1994
DOI: 10.1038/sc.1994.57
|View full text |Cite
|
Sign up to set email alerts
|

Penile prostheses for the management of the neuropathic bladder and sexual dysfunction in spinal cord injury patients: long term follow up

Abstract: During the last 10 years, 90 penile prostheses were implanted in 82 patients with spinal cord injury. Surgery was done 1 month to 25 years (average 4.8 years) after the injury. The follow up period ranged from 1 to 10 years (average 4 years). A prosthesis was implanted for urinary management in 51 patients (62%), for sexual dysfunction in 10 patients (12%) and for both purposes in 21 patients (26%). Ninety-three per cent of the patients who used the implant for urinary management and 64% of the patients who us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 9 publications
1
26
0
3
Order By: Relevance
“…A previous report indicated an improvement in QoL with a vacuum erection device but a loss of erection during sexual activity, resulting in 67% discontinuation of treatment in the sample population. 36 Penile prostheses and prostaglandin E 1 treatment improved the QoL of patients with SCI as well; however, for patients with SCI and ED, complications resulted from penile implants and prostaglandin E 1 treatment, 6,36,37 underscoring the importance of an eective and noninvasive treatment for ED.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report indicated an improvement in QoL with a vacuum erection device but a loss of erection during sexual activity, resulting in 67% discontinuation of treatment in the sample population. 36 Penile prostheses and prostaglandin E 1 treatment improved the QoL of patients with SCI as well; however, for patients with SCI and ED, complications resulted from penile implants and prostaglandin E 1 treatment, 6,36,37 underscoring the importance of an eective and noninvasive treatment for ED.…”
Section: Discussionmentioning
confidence: 99%
“…3,10 Treatment options for ED in patients with SCI include intracavernosal injection of vasoactive substances, VCD and surgical implantation of penile prothesis. 3,6,8 The American Urological Association Panel on the treatment of organic ED stated that the ultimate goal is a therapy that is reliable, has minimal side effects and is simple to use. 9 Sildenafil appears to meet these specifications.…”
Section: Discussionmentioning
confidence: 99%
“…3 Patients also tend to reject the use of external VCD because they want to have more naturally occurring erections within the context of sexual stimulation by a partner. 8 Derry et al, 2 however, reported that sildenafil is efficacious and well tolerated by SCI patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Any man with SCI, regardless of age, cause, or level and extent of injury, may be treated with these methods while bearing in mind the absolute or relative contraindications for each treatment method.…”
Section: Third-line Treatmentsmentioning
confidence: 99%